Analisis Pengaruh Ukuran Perusahaan, Profitabilitas, Leverage, Kepemilikan Institusional dan Kepemilikan Manajerial terhadap Carbon Emission Disclosure - Andini Eleshya Putri; Warnida Warnida (Jurnal Akuntansi dan Keuangan, 2023)
The objective of this study is to examine factors that influence the Carbon Emission Disclosure. Several factors, such as size firm, profitability, leverage, institutional ownership, and managerial ownership are included in this study. The population used in this research is all manufacturing companies listed on the Indonesia Stock Exchange during 2019-2021. The sampling technique applied was purposive sampling and based on predetermined criteria obtained a sample of 22 companies. Data analysis method in this research is multiple linear regression. The results show that size firm, profitability, and leverage have a significant effect on Carbon Emissions Disclosure. Meanwhile, institutional ownership and managerial ownership have no significant effect on Carbon Emission Disclosure.